Literal Translation, Sacred Scripture and Kitab Malay - Riddell, Peter G. (Studia Islamika, 2002)
The study of Malay dialects was a specialist concern during the period of Dutch colonization of Indonesia and British colonization of the Malay peninsular. In recent times, the Malaysian National Language Council, the Dewan Bahasa dan Pustaka, and its Indonesian counterpart, the Pusat Pembinaan dan Pengembangan Bahasa (PPPB), have devoted considerable resources to the study of Malay dialectology. Such dialect studies have necessarily had a geographical focus, by way of descriptive grammars of Malay dialects spoken in particular areas. Examples are the studies of Pontianak Malay (Kamal et. al' 1986) and Palembang Malay (Aliana et. al. 1987) published by the PPPB.DOI: 10.15408/sdi.v9i1.672